A field trial to assess action thresholds for management of Bactericera cockerelli in main crop processing potatoes at Pukekohe - Walker, G.P.; MacDonald, F.H.; Puketapu, A.J.; Wright, P.J.; Connolly, P.G.; Anderson, J.A.D. (New Zealand Plant Protection, 2013)
A main crop summer potato trial at Pukekohe assessed the damage caused by Bactericera cockerelli tomato potato psyllid (TPP) and investigated the use of action spray thresholds Five treatments were used infurrow insecticide and weekly blocks of foliar sprays; infurrow insecticide and one of three different thresholdbased foliar spray programmes; and no insecticides The thresholdbased spray programmes used either the number of TPP nymphs per middle leaf or the mean number of TPP adults per yellow sticky trap per week plus different modeofaction insecticide rotations Three treatments resulted in acceptable yield and specific gravity and a low incidence of zebra chip disease (ZC) These were the weekly treatment and two spray programmes based on a threshold of >3 TPP adults per trap per week where insecticide applications were reduced by 50 compared to the weekly applications